Integrative Didactic Approaches To The Development Of Students’ Linguistic Competence In Higher Education - Khakimova M.M (TLEP – International Journal of Multidiscipline, 2025)
The development of students’ linguistic competences remains a central focus in modern language education. In the age of globalization, the ability to communicate effectively in a foreign language is not only a linguistic necessity but also a key component of intercultural competence and professional success. This paper explores theoretical and methodological foundations of linguistic competence formation, emphasizing the views of L. T. Ahmedova, who underlines the importance of didactic principles in the language learning process. It analyses communicative, cognitive, competency-based, and differential approaches as essential dimensions for shaping linguistic competence. The article concludes that an integrative didactic model that combines these approaches fosters deep, meaningful, and sustainable language learning.